ANALISIS PENGGUNAAN TEKNOLOGI MULTI-CONSTELLATION GNSS DALAM SISTEM NAVIGASI UDARA - Wahyu Wira Bhaskara; M Arif Sulaiman; Eriyandi (Jurnal Manajemen Dirgantara, 2024)
Global Navigation Satellite System (GNSS) technology has become a crucial component in modern aviation navigation systems. GNSS enables aircraft to determine their location, altitude, and speed with high precision, even in challenging environments. Currently, several GNSS satellite constellations are in operation, such as GPS, GLONASS, BeiDou, and Galileo. The use of multi-constellation GNSS technology in aviation navigation systems offers several significant advantages, including enhanced accuracy, availability, and resilience to interference. This study discusses the benefits and challenges of integrating multi-constellation GNSS in aviation navigation, as well as its implications for flight safety and operational efficiency. The analysis results indicate that the implementation of multi-constellation GNSS can reduce the risk of navigation errors and improve the overall performance of navigation systems.